«MUSLIMS OF FRANCE» AND «MUSLIM BROTHERHOOD»: UNSPOKEN PARTNERSHIP - Alexey V. Chistyakov (Научно-аналитический вестник Института Европы РАН, 2022)
The Russian scientific community stills have interest in «Muslim brotherhood» movement. In particular, this interest is connected with the rejection of a number of organizations affiliated with «Muslim brotherhood» in the French Republic to sign the «Charter of Principles». It is known that the foreign press and Russian scientists have repeatedly noted the fact of the connection of some religious organizations in France with «Muslim brotherhood», but scientific literature in Russian pays insufficient attention to how this connection is implemented. In this paper, the author reveals some channels of interaction between the Islamic community of France and «Muslim brotherhood». In addition, the author will show how Muslim Brothers use «Muslims of France» (former «Union of Islamic Organizations of France») as the foremost propagators of their values and ideas. Including in the political space of the Fifth Republic.